Research in Personnel and Human Resources Management. - Buckley, M. Ronald (Research in Personnel and Human Resources Management Ser., 2018)
Research in Personnel and Human Resources Management is designed to promote theory and research on important substantive and methodological topics in the field of human resources management. Volume 36 focuses on key issues such as job search processes, human resource technology systems, pregnancy issues at work, and emotions at work.